The changing role of the exchange rate in a globalised economy - Filippo di Mauro; Rasmus Rüffer; Irina Bunda (European Central Bank (ECB), 2008)
In addition to its direct effects on the global trading and production structure, the ongoing process of globalisation may have important implications for the interaction of exchange rates and the overall economy. This paper presents evidence regarding possible changes in the role of exchange rates in a more globalised economy. First, it analyses the link between exchange rates and prices, showing that there is at most a moderate decline in exchange rate pass-through for the euro area. Next, it turns to the effect of exchange rate changes on trade flows. The findings indicate that the responsiveness of euro area exports to exchange rate changes may have declined somewhat as a result of globalisation, reflecting mainly shifts in the geographical and sectoral composition of trade flows. The paper also provides a firm-level analysis of the impact of exchange rate changes on corporate profits, which suggests that overall this relationship appears to be relatively stable over time, although there are important crosscountry differences. In addition, it studies the overall impact of exchange rates on GDP and the potential role of valuation effects as a transmission channel in the case of the euro area.
Keywords: E3; F15; F31; 330; Globalisation; exchange rate; trade exchange rate pass-through; valuation effects.; Wechselkurs; Euro; Exchange Rate Pass-Through; Geldpolitische Transmission; Nationaleinkommen; Gewinn; Globalisierung; EU-Staaten